Paleobiogeography of late Cretaceous ammonoids - Ifrim, Christina; Lehmann, Jens; Ward, Peter M. (Ammonoid paleobiology: from anatomy to ecology, 2015)
Ammonoids were dominant elements of marine Cretaceous faunas. Their fossils are important biostratigraphic indicators, in some cases with worldwide distribution. Their paleobiogeographic distributions were influenced by changing continental positions, currents, sea level change, and perhaps by their mode of life as reflected in the evolution of many diverse lineages of heteromorphic, possibly rather vertically migrating than horizontally swimming taxa through the Cretaceous. Here, we review the current paleobiogeographic understanding of Late Cretaceous ammonoid distribution in an effort to complement and add to previous work in this field. Four principal paleobiogeographic areas can be distinguished in the Cretaceous: The Boreal Realm, the Tethyan Realm, the Pacific Realm, and the Austral Realm. A Tethyan Superrealm is repeatedly recognized throughout the Late Cretaceous, although represented by varying taxa. Migration between the realms and provinces appears to be linked to changes of migration routes, triggered by sea level changes. At the end of the Cretaceous, provincialism disappears, preceding the extinction of the Ammonoids.